The impact of generalized joint laxity on clinical outcomes of total knee arthroplasty - Kwon, Sae Kwang (Knee Surg Sports Traumatol Arthrosc, 2017)
PURPOSE: The aim of this study was to investigate whether the severity of generalized joint laxity influences preoperative and postoperative clinical outcomes and if patients with severe generalized joint laxity would require a thicker polyethylene (PE) liner during total knee arthroplasty (TKA). METHODS: A total of 338 female patients undergoing TKA were divided into two groups according to generalized joint laxity. Preoperative and postoperative (at 3 years) patellofemoral scale, AKS, WOMAC, ROM, and satisfaction VAS were compared between the two groups. Additionally, PE liner thickness was compared. RESULTS: Preoperatively, flexion contracture and WOMAC stiffness scores in the severe laxity group were significantly lower than those in the no to moderate laxity group (p < 0.001 for both). There was no significant difference in postoperative clinical outcomes of patellofemoral scale, AKS, WOMAC, or ROM or in satisfaction VAS between the two groups. There was a significant difference in PE liner thickness between the two groups (10.3 ± 1.3 versus 11.4 ± 1.2, p = 0.043). CONCLUSIONS: There was no significant difference of clinical outcomes between the patients with and without severe generalized joint laxity after 3 years of follow-up after TKA, even though preoperative clinical outcomes indicated that the patients with severe generalized joint laxity showed significantly smaller flexion contraction and better WOMAC stiffness score. Since patients with generalized joint laxity require a thicker PE liner, care should be taken to avoid cutting too much bone from patients with severe generalized joint laxity. LEVEL OF EVIDENCE: Retrospective comparative study, Level III.